Responda:
Explicação:
Do primeiro multiplicador,
Responda:
Explicação:
# "note que para x = 2" #
#2^3-6(2)^2+16=0#
#rArr (x-2) "é um fator" #
# "dividindo" x ^ 3-6x ^ 2 + 16 "por" (x-2) #
#color (vermelho) (x ^ 2) (x-2) cor (magenta) (+ 2x ^ 2) -6x ^ 2 + 16 #
# = cor (vermelho) (x ^ 2) (x-2) cor (vermelho) (- 4x) (x-2) cor (magenta) (- 8x) + 16 #
# = cor (vermelho) (x ^ 2) (x-2) cor (vermelho) (- 4x) (x-2) cor (vermelho) (- 8) (x-2) cancelar (cor (magenta) (- 16)) cancelar (+16) #
# rArrx ^ 3-6x ^ 2 + 16 = 0 #
#rArr (x-2) (x ^ 2-4x-8) = 0 #
# "solve" x ^ 2-4x-8 "usando a fórmula quadrática" cor (azul) "#
# "com" a = 1, b = -4 "e" c = -8 #
# x = (4 + -sqrt (16 + 32)) / 2 #
#color (branco) (x) = (4 + -sqrt48) / 2 = (4 + -4sqrt3) / 2 = 2 + -2sqrt3 #
#rArr (x-2) (x ^ 2-4x-8) = 0 #
# "tem soluções" x = 2, x = 2 + -2sqrt3 #